2006
DOI: 10.1021/jf062467k
|View full text |Cite
|
Sign up to set email alerts
|

Steamed American Ginseng Berry:  Ginsenoside Analyses and Anticancer Activities

Abstract: This study was designed to determine the changes in saponin content in American ginseng berries after treatment by heating and to assess the anticancer effects of the extracts. After steaming treatment (100-120 degrees C for 1 h, and 120 degrees C for 0.5-4 h), the content of seven ginsenosides, Rg1, Re, Rb1, Rc, Rb2, Rb3, and Rd, decreased; the content of five ginsenosides, Rh1, Rg2, 20R-Rg2, Rg3, and Rh2, increased. Rg3, a previously identified anticancer ginsenoside, increased significantly. Two hours of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
125
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 165 publications
(135 citation statements)
references
References 36 publications
9
125
0
1
Order By: Relevance
“…Instead, many efforts have been made to get ginseng with higher concentrations of effector ginsenosides toward therapeutic use. Studies with steamed ginseng showed that it has higher concentration of Rh1, Rg2, Rg3, and Rh2, and, in parallel, augments the anti-proliferative effects on various cancer cell lines (Kim et al, 2000;Wang et al, 2006). Contents of ginsenosides from the fermented ginseng extract prepared by incubation of ginsenoside-β-glucosidase are also quite different from those of crude ginseng extract.…”
Section: Doimentioning
confidence: 99%
“…Instead, many efforts have been made to get ginseng with higher concentrations of effector ginsenosides toward therapeutic use. Studies with steamed ginseng showed that it has higher concentration of Rh1, Rg2, Rg3, and Rh2, and, in parallel, augments the anti-proliferative effects on various cancer cell lines (Kim et al, 2000;Wang et al, 2006). Contents of ginsenosides from the fermented ginseng extract prepared by incubation of ginsenoside-β-glucosidase are also quite different from those of crude ginseng extract.…”
Section: Doimentioning
confidence: 99%
“…The ginseng berry has many unique bioactive constituents compared to the generally used ginseng root. Through various assays [13,[119][120][121][122] …”
Section: Exploring Other Bioactive Constituents In the Ginseng Berry mentioning
confidence: 99%
“…Unlike the widely used ginseng root, the ginseng berry is preserved for planting and has not been used by general populations. A recent study reported that the ginseng leaf and berry have higher levels of ginsenosides than ginseng root, and their pharmacological activities have also been reported [13]. In this review, we will summarize the research on the role of dietary ginseng berries in delaying aging, as well as evidence suggesting positive biological effects to prevent age-related diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent pilot study, we observed that steaming the American ginseng berry changed its chemical composition. 15) However, the anticancer effects of ginseng berry have not been systematically studied, and observed in vivo. In addition, the effects of heat treatment on the ginsenoside content of ginseng berry extract have not been determined.…”
mentioning
confidence: 99%